THE PROBLEM OF TRANSLATING SPEECH EXPRESSIONS IN THE TRANSLATIONS OF ABDULLA QADIRI'S NOVEL "SCORPION FROM THE ALTAR" (Academicia Globe: Inderscience Research, 2024)
To know the language of a certain nation means to understand its whole existence. No researcher can carry out his research without knowing the language and culture of the country under study. Speech expressions do not appear in language by themselves. There are a number of factors that shape them. First of all, national characteristics, nationality, customs of the nation are one of the main tools. Because every nation has its own speech expressions. Based on this, first of all, we should consider national customs and traditions as the most important factors that create speech expressions.